Numerical simulation of sheet metal blanking based on fully coupled elastoplasticity-damage constitutive equations accounting for yield surface distortion-induced anisotropy. (September 2017) - Yue, Zhenming; Badreddine, Houssem; Saanouni, Khemais; Zhuang, Xincun; Gao, Jun
This paper deals with the numerical simulation of sheet metal blanking process based on fully coupled elastoplastic model accounting for the induced anisotropies due to the kinematic hardening and the yield surface distortion. The yield surface distortion is assumed to be controlled by the kinematic hardening leading additional extra hardening which enhances the predictive capabilities of the model. Series of finite element-based numerical simulations of blanking process with four kinds of assumed distortional hardening parameters have been conducted. Through the comparison between the experimentally observed responses and the numerically predicted ones with and without the yield surface distortion effect, the significance of the yield surface distortion-induced anisotropy on the estimation of the blanking edge quality has been investigated.